Electrochemical Analysis of Acrylamide Using Screen‐Printed Carboxylated Single‐Walled Carbon Nanotube Electrodes. Issue 5 (15th April 2014) - González‐Fuentes, Fanny Jaqueline; Manríquez, J.; Godínez, Luis A.; Escarpa, Alberto; Mendoza, Sandra
Abstract Acrylamide (AA) was electrochemically detected and quantified by means of its voltammetric response on carboxylic modified Single‐Walled Carbon Nanotube Screen Printed Electrodes (COOH‐SWCNT‐SPEs). The electroreduction signal of AA was proportional to AA concentration at low values (below 300 µM) and the observed sensitivity was explained in terms of AA adsorption on the COOH‐SWCNT‐SPEs that was demonstrated using the electrochemical response of [Fe(CN)6]3− and [Fe(CN)6]4− and Raman spectroscopy experiments. In order to test the suggested analytic approach (LOD of 0.03 µM, LOQ of 0.04 µM), detection and quantification of AA in fried potatoes was carried out using the proposed electrochemical method and HPLC. Both techniques showed similar contents of AA.